Does localization of demyelinating lesions influence the intensity of back pain and quality of life in patients with relapsing-remittent multiple sclerosis? A cross-sectional study - S. Liguori; M. Paoletta; A. Moretti; G. Barra; F. Gimigliano; G. Iolascon (Verduci Editore, 2024)
Objective: Pain is a frequently reported symptom in patients with Multiple Sclerosis (MS), often linked to demyelinating lesions seen on magnetic resonance imaging (MRI) in the brainstem or spinal cord. Individuals with MS may also experience nociceptive or musculoskeletal pain, particularly low back pain (LBP). This study sought to assess the impact of the location of demyelinating lesions on the severity of back pain and on the quality of life (QoL) in patients with relapsing-remitting MS. Patients and Methods: Patients with relapsing-remitting MS who experienced low back pain were included in the study and divided into two groups based on the location of demyelinating lesions found on MRI scans: Group A (cerebral, cerebellar, and spinal lesions) and Group B (cerebral and spinal lesions). All participants underwent assessments for pressure pain threshold using Fisher's algometer, evaluations for pain intensity and interference with daily activities using the Brief Pain Inventory (BPI) Severity Index and Interference Index. Additionally, physical disability was measured using the Modified Barthel Index, and QoL was assessed using both the European Quality of Life-5 Dimensions-3 Levels index and European Quality of Life-Visual Analogue Scale. Results: Ten multiple sclerosis patients were recruited, with 6 participants in Group A and 4 in Group B. A significant difference was observed in PPT scores using Fisher's algometer, revealing lower scores in the group with cerebellar lesions. Conclusions: Our findings suggest that cerebellar demyelinating lesions may affect pain threshold intensity, though the effects on activities of daily living (ADLs) and perceived health-related quality of life (HRQoL) are still under debate.